2015
DOI: 10.5958/0974-0112.2015.00039.0
|View full text |Cite
|
Sign up to set email alerts
|

Influence ofAzotobacterand vermicompost on growth, flowering, yield and quality of strawberry cv. Chandler

Abstract: An experiment was carried out during two subsequent years, i.e., 2009-10 and 2010-11 to study the influence of Azotobacter, vermicompost on growth, flowering, yield and quality of strawberry cv. Chandler. There were nine treatments comprising two levels each of Azotobacter (6 and 7 kg/ha) and vermicompost (20 and 30 t/ ha) and their combinations along with one control, replicated thrice in randomized block design. Five kg of FYM was applied as a basal dose in all the treatments including control. All the doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 2 publications
17
5
0
Order By: Relevance
“…The earliness may be due to an optimum supply of plant nutrients growth harmones in right amount during the entire crop period which induces the vegetative development of the plant and ultimately more photosynthesis. Similar findings also reported by Karma Beer et al, (2017), Rayees et al, (2015), Tripathi et al, (2015), Yadav et al, (2010), Umer et al, (2010), Singh et al,(2010), Singh (2009), Asrey andSingh (2004) and Gajbhiye et al, (2003) all reported the superiority of organic manures compared to NPK inorganic fertilizers in producing higher yields. The superiority of treatment T4 in producing a maximum number of fruits/plant may be due to a greater growth and reproductive capacity of plants as influenced by a mixture of manures and inorganic fertilizers.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The earliness may be due to an optimum supply of plant nutrients growth harmones in right amount during the entire crop period which induces the vegetative development of the plant and ultimately more photosynthesis. Similar findings also reported by Karma Beer et al, (2017), Rayees et al, (2015), Tripathi et al, (2015), Yadav et al, (2010), Umer et al, (2010), Singh et al,(2010), Singh (2009), Asrey andSingh (2004) and Gajbhiye et al, (2003) all reported the superiority of organic manures compared to NPK inorganic fertilizers in producing higher yields. The superiority of treatment T4 in producing a maximum number of fruits/plant may be due to a greater growth and reproductive capacity of plants as influenced by a mixture of manures and inorganic fertilizers.…”
Section: Resultssupporting
confidence: 77%
“…Present findings are in close conformity with the results presented by Rayees et al, (2015), Tripathi et al, (2015), Singh and Dwivedi (2011), Shehata et al, (2011), Abu-Zahra et al, (2011), Yadav et al, (2010, Mahadeen et al, (2009), Aracon et al, (2004, Ali et al, (2003), Prasad et al, (2002), Singh et al, (2001) and Woznaik et al, (1997).…”
Section: The Experiments Was Laid Out In a Randomizedsupporting
confidence: 83%
“…This phenomenon may be on account of prolonged growth of plant in the presence of organic, inorganic and biofertilizers. These results gain support from the findings of Tripathi et al, (2015), who observed earliest flowering with vermicompost + Azotobacter which are also in close conformity with the findings of Kumar et al, (2007) in tomato. Data presented in table 2 clearly revealed that minimum number of days taken to fruit set (6.26) and maximum number of fruits set per plant (42.09) was recorded in plants treated with vermicompost (25ton/ha) + Azotobacter (6 kg/Ha) + NPK (70:80:80) treated plants.…”
Section: Floral Characterssupporting
confidence: 82%
“…Similar findings also reported by Yadav et al, (2010) and Umar et al, (2010) in strawberry. These results are in conformity with the finding of Tripathi et al, (2015) who noted that increase in vermicompost and Azotobacter doses resulted in maximum fruit set in strawberry.…”
Section: Floral Characterssupporting
confidence: 81%
“…And it also depends on the different condition of the growing strawberry in poly house (Tripathi et al, 2015). In plant height at 30 days observation shows the 10.62% increase at 15 days; however the variation in treatments from 4.06-5.93 cm and T 9 (25% RDF + 75% FYM) shows the best plant height.…”
Section: Resultsmentioning
confidence: 99%